Heterostructure composite material with high shielding effectiveness as well as preparation method and application of heterostructure composite material

The heterostructure nanocomposite material of niobium pentoxide and trivalent iron oxide was synthesized by the dual hydrothermal method, which solved the problems of the existing radar absorbing materials in the balance of conductivity and magnetic properties, and achieved high shielding efficiency and low microwave reflectivity.

CN119706956AActive Publication Date: 2025-03-28SHAOXING ZHU OVERSEAS TALENT CLUSTER DEVELOPMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411868784.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

While existing radar wave absorbing materials improve shielding efficiency, they are difficult to balance the conductivity and magnetic properties, resulting in reduced performance and increased electromagnetic interference sensitivity.

Method used

The heterostructure nanocomposite material of niobium pentoxide and trivalent iron oxide was synthesized by double hydrothermal method, and the overall shielding efficiency of the material was improved by using its synergistic action and morphological regulation.

Benefits of technology

The shielding efficiency of the material is significantly improved, and through the synergistic effect of dielectric and magnetic loss, efficient electromagnetic wave absorption and reflection are achieved, and microwave reflectivity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706956A_ABST
    Figure CN119706956A_ABST
Patent Text Reader

Abstract

The invention discloses a heterostructure composite material with high shielding effectiveness as well as a preparation method and application thereof, and the preparation method comprises the following steps: S1, mixing Nb2O5, FeCl3. 6H2O and Na2SO4. 10H2O in deionized water according to a certain proportion to obtain a uniform solution; and S2, transferring the uniform solution obtained in the step S1 into a closed container, carrying out constant-temperature heating treatment, then carrying out annealing treatment in an air environment to obtain a precipitate, cooling the precipitate to room temperature, and carrying out centrifugation and washing to obtain the NF heterostructure nano composite material. According to the heterostructure composite material with high shielding effectiveness and the preparation method and application thereof, the NF heterostructure nano composite material is synthesized through a double-hydrothermal method, and the overall shielding effectiveness of the NF heterostructure nano composite material is remarkably improved through the synergistic effect of niobium pentoxide and ferric iron oxide and form regulation and control; the method has important value in the modern electronic and technical fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano composite materials, and in particular to a heterogeneous structure composite material with high shielding effectiveness, a preparation method and an application thereof. Background Art

[0002] Radar absorbing materials (RAMs) have been gaining importance as an integral component in both tactical and defensive applications. More specifically, RAMs are able to absorb radiation, thereby shielding or scatter radiation, thereby achieving stealth to avoid detection. The degree of shielding or scattering is usually quantified by shielding effectiveness (SE). Typically, the total shielding effectiveness (SET) of RAMs is defined as their ability to absorb, reflect, and transmit incident radiation. In tactical scenarios, the degree of shielding or scattering is usually expressed by radar cross section (RCS).

[0003] In principle, the most effective RAMs should possess both electrical conductivity and magnetic properties, however, excessively high electrical conductivity may unexpectedly enhance reflection-based SE, which is undesirable in RAMs applications. In addition, in today's technological environment, the rapid expansion of electronic devices and their operation at high frequencies further increase the susceptibility to electromagnetic interference (EMI). As a result, severe performance degradation and failures occur from time to time. Therefore, there is an urgent need to develop effective EMI shielding materials.

[0004] Traditional shielding solutions often struggle to find the best compromise between performance, weight, and flexibility, which has led to the need for new alternative materials. New alternative materials, such as metal oxide heterostructures, are expected to alleviate the limitations of traditional solutions while further enhancing their electromagnetic shielding capabilities.

[0005] In the prior art, various forms of metal oxide heterostructures have been synthesized, including nanorods (NRs), nanoparticles (NPs), nanospheres, nanofibers and nanobelts. The synthesis techniques include thermal oxidation, plasma oxidation, sol-gel method, chemical precipitation method, forced hydrolysis method, pulsed laser deposition, chemical vapor deposition, template-assisted method, high-energy ball milling, electrospinning and hydrothermal method. Among them, the hydrothermal method has been proven to be particularly advantageous because of its simple process, low cost and low temperature treatment, which helps promote the development of single-crystalline oxide nanostructures. With the increasing demand for effective EMI shielding in industries that require high electromagnetic interference protection, the urgency of finding new shielding materials continues to rise. Summary of the invention

[0006] The purpose of the present invention is to provide a heterostructure composite material with high shielding effectiveness, a preparation method and an application thereof. The NF heterostructure nanocomposite material is synthesized by a double hydrothermal method. The synergistic effect of niobium pentoxide and trivalent iron oxide and the morphology regulation significantly improve its overall shielding effectiveness, which has important value in the fields of modern electronics and technology.

[0007] To achieve the above object, the present invention provides a method for preparing a heterogeneous structure composite material with high shielding effectiveness, comprising the following steps:

[0008] S1. Mix Nb2O5, FeCl3·6H2O and Na2SO4·10H2O in deionized water in a certain proportion to obtain a uniform solution;

[0009] S2. The uniform solution obtained in S1 is transferred to a sealed container, subjected to a constant temperature heating treatment, and then subjected to an annealing treatment in an air environment to obtain a precipitate, which is cooled to room temperature, and then centrifuged and washed to obtain a NF heterostructure nanocomposite material.

[0010] Preferably, in S1, the mass ratio of the Nb2O5, the FeCl3·6H2O, the Na2SO4·10H2O and the deionized water is 0.05-0.15g: 0.01-0.02g: 0.05-0.07g: 25-35ml.

[0011] Preferably, in S2, the constant temperature heating treatment is specifically:

[0012] Maintain the temperature within the range of 160°C to 200°C for 10h to 14h.

[0013] Preferably, in S2, the annealing treatment is specifically:

[0014] Annealing is performed at a heating rate of 1°C / min to 3°C / min in a temperature range of 450°C to 550°C for 2h to 4h.

[0015] Preferably, in S2, the washing is performed multiple times using ethanol and deionized water.

[0016] To achieve the above object, the present invention also provides a NF heterostructure nanocomposite material.

[0017] To achieve the above objectives, the present invention also provides an application of the NF heterostructure nanocomposite material in capacitors, insulators and other electronic components.

[0018] Preferably, the NF heterostructure nanocomposite material is embedded in a silicone elastomer matrix by mechanical mixing and solution mixing techniques to obtain a sample for electromagnetic shielding.

[0019] Preferably, the method comprises the following steps:

[0020] Step 1: Mixing a polymer matrix and a curing agent in a certain proportion to prepare a silicon solution;

[0021] Step 2: Add the NF heterostructure nanocomposite material into the silicon solution, perform dispersion treatment and then solidify to obtain a sample.

[0022] Preferably, step 2 is specifically as follows:

[0023] The NF heterostructure nanocomposite was incorporated into the silicon solution and internally mixed at 180 rpm for 30 min to obtain a NF / silicon mixture with particles uniformly dispersed in the silicon matrix, and then cured at 100 °C / min for 25 min to obtain a NF heterostructure nanocomposite / silicone elastomer.

[0024] Therefore, the present invention adopts the above-mentioned heterogeneous structure composite material with high shielding effectiveness, preparation method and application, and the beneficial effects are as follows:

[0025] (1) The present invention utilizes the synergistic effect of Nb2O5 (niobium pentoxide) and α-Fe2O3 (hematite or trivalent iron oxide) to provide better dielectric properties, help effectively dissipate energy and achieve ultra-low microwave reflection by effectively absorbing electromagnetic waves, thereby enhancing the overall shielding effectiveness. In addition, morphology control can increase the number of interactions between the material surface and electromagnetic radiation, further improving the shielding effect.

[0026] (2) The present invention uses Nb2O5 nanoparticles (NPs) as a powerful interface polarization source, while α-Fe2O3 nanorods (NRs) form a large conductive network, which enables electronic conductive hopping between Nb2O5NPs. In addition, the huge gaps within the Nb2O5NPs provide multiple scattering events, further enhancing the dissipation process of electromagnetic waves. By enhancing the effective absorption brought about by these mechanisms and balancing the conduction loss and reflection loss by achieving an optimal conductivity, a nanocomposite material with superior shielding effect and abnormally low microwave reflectivity is developed.

[0027] (3) The synergistic effect of the dielectric loss caused by the Nb2O5 nanoparticles of the present invention and the magnetic loss caused by the α-Fe2O3 nanorods ensures that most of the incident electromagnetic energy is slowed down and converted into heat or other non-electromagnetic forms of energy. This dual loss mechanism maximizes the dissipation of energy through the complementary manner of electrical and magnetic paths, and plays a vital role in the superior electromagnetic interference shielding performance.

[0028] (4) The synergistic effect, dipole polarization, interface polarization, microcapacitance effect and conductive loss between the two metal oxides of the present invention open up broad prospects for further high-performance application research and development, including random access memory (RAM) technology and effective electromagnetic interference shielding solutions, and provide a reasonable synthesis route for exploring advanced functional materials, opening up a new research window.

[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a scanning electron microscope image of a heterogeneous structure composite material with high shielding effectiveness, a preparation method and an application example, wherein (a) is comparative example 1, (b) is comparative example 2, and (c) is example 1;

[0031] Figure 2 It is a transmission electron microscope image of Example 1 of a heterogeneous structure composite material with high shielding effectiveness of the present invention, wherein (a) is a transmission electron microscope image at 100nm, and (b) is a transmission electron microscope image at 200nm;

[0032] Figure 3 The present invention is a complex dielectric constant and complex permeability spectrum of a heterogeneous structure composite material with high shielding effectiveness, a preparation method and an application embodiment, wherein (a) is a real part spectrum of the complex dielectric constant in the X-band, (b) is an imaginary part spectrum of the complex dielectric constant in the X-band, (c) is a real part spectrum of the complex permeability in the X-band, and (d) is an imaginary part spectrum of the complex permeability in the X-band;

[0033] Figure 4 It is a frequency-dependent variation diagram of a heterogeneous structure composite material with high shielding effectiveness, a preparation method and an application embodiment of the present invention, wherein (a) is the dielectric loss tangent, and (b) is the magnetic loss tangent;

[0034] Figure 5 1 is a Cole-Cole diagram of an embodiment of a heterogeneous structure composite material with high shielding effectiveness of the present invention, wherein (a) is comparative example 1, (b) is comparative example 2, and (c) is embodiment 1;

[0035] Figure 6 It is a comparison diagram of the frequency dependence of electromagnetic shielding effectiveness (EMI SE) of a heterogeneous structure composite material with high shielding effectiveness of the present invention, a preparation method and an application embodiment. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0037] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0038] Embodiment 1

[0039] A method for preparing a heterogeneous structure composite material with high shielding effectiveness comprises the following steps:

[0040] S1. Mix 0.1 g of pre-synthesized Nb2O5, 0.016 g of FeCl3·6H2O and 0.06 g of Na2SO4·10H2O in 30 mL of deionized water to obtain a uniform solution;

[0041] S2. The uniform solution obtained in S1 was transferred to a polytetrafluoroethylene-lined reactor, maintained at 180°C for 12 h, and then annealed at 500°C for 3 h in an air environment at a heating rate of 2°C / min to improve the crystallinity of the heterostructure. The precipitate was cooled to room temperature, separated by centrifugation and washed with ethanol and deionized water to obtain the NF (Nb2O5NPs@α-Fe2O3NRs) heterostructure nanocomposite material.

[0042] Comparative Example 1

[0043] A preparation method of Nb2O5 NPs heterostructure nanomaterials, specifically:

[0044] 0.1 g of pre-synthesized Nb2O5 was mixed with 30 mL of deionized water to obtain a uniform solution, which was transferred to a polytetrafluoroethylene-lined reactor and maintained at 180°C for 12 h, and then annealed at 500°C for 3 h in an air environment at a heating rate of 2°C / min to improve the crystallinity of the heterostructure. The precipitate was cooled to room temperature, and the Nb2O5 NPs heterostructure nanomaterials were obtained by centrifugation and washed with ethanol and deionized water.

[0045] Comparative Example 2

[0046] A preparation method of α-Fe2O3 NRs heterostructure nanomaterial, specifically:

[0047] 0.016 g of FeCl3·6H2O and 0.06 g of Na2SO4·10H2O were mixed in 30 mL of deionized water to obtain a uniform solution, which was transferred to a polytetrafluoroethylene-lined reactor and maintained at 180°C for 12 h. It was then annealed at 500°C for 3 h in an air environment at a heating rate of 2°C / min to improve the crystallinity of the heterostructure. The precipitate was cooled to room temperature, separated by centrifugation and washed with ethanol and deionized water to obtain α-Fe2O3 NRs heterostructure nanomaterials.

[0048] Experimental Testing

[0049] like Figure 1 As shown, Figure 1 (a) shows Nb2O5 nanoparticles with a highly porous structure and aggregated morphology. The porous structure of Nb2O5 nanoparticles provides a large surface area that can effectively interact with electromagnetic waves. The high surface area to volume ratio helps scatter and absorb electromagnetic radiation, thereby improving the shielding effect. In addition, the porous nature of these particles may lead to multiple reflections inside the material, which is an ideal property for absorbing electromagnetic waves.

[0050] Figure 1 (b) shows a more compact and angular morphology of α-Fe2O3 nanorods. These regular geometries indicate that the growth was controlled by the hydrothermal process and that the parameters were chosen to achieve preferential crystal growth along a specific axis. α-Fe2O3 nanorods exhibit a compact and ordered structure, which contributes to their anisotropic electromagnetic properties. The directionality of these nanorods can be used to tailor the electromagnetic wave propagation path inside the shielding material so that it interacts optimally with the incident electromagnetic wave.

[0051] Figure 1 (c) is a NF heterostructure nanocomposite material. The arrows indicate the interconnected disordered agglomerates connected by extended rod-like structures. The heterostructure formed by Nb2O5 nanoparticles and α-Fe2O3 nanorods shows a morphology in which nanoparticles are uniformly attached to the surface of nanorods, which can enhance the interfacial interaction between the two phases, thereby improving charge separation and migration. Figure 2 As shown, the interface between α-Fe2O3 nanorods and Nb2O5 nanoparticles exhibits obvious recognition features, indicating good formation of the composite material. This indicates that the current dual hydrothermal synthesis method is effective in integrating the two materials into a composite form, demonstrating its improved synergistic properties.

[0052] In addition, the combination of the properties of Nb2O5 nanoparticles and α-Fe2O3 nanorods may produce a synergistic effect in electromagnetic shielding. The nanocomposite can take advantage of the electrical conductivity and magnetism of α-Fe2O3 and the dielectric properties of Nb2O5 to provide a broad-spectrum electromagnetic shielding effect, achieving the shielding effect by combining reflection, absorption and multiple scattering mechanisms.

[0053] The materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively embedded in a silicone elastomer matrix by mechanical mixing and solution mixing techniques to obtain NF heterostructure nanocomposite materials / silicone elastomer, Nb2O5 nanoparticles / silicone elastomer and α-Fe2O3 nanorods / silicone elastomer, and electromagnetic measurement tests were carried out and analyzed by relative complex dielectric constant and complex permeability.

[0054] Preparation of NF heterostructure nanocomposites / organic silicon elastomer, Nb2O5 nanoparticles / organic silicon elastomer and α-Fe2O3 nanorods / organic silicon elastomer, the specific steps are as follows:

[0055] First, by adding Dow Corning SYLGARD TM The polymer matrix and curing agent of the 184 Silicon Encapsulant Transparent Kit were thoroughly mixed in a weight ratio of 10:1 to prepare a silicon solution. The prepared NF heterostructure nanocomposite was then incorporated into the silicon solution. Subsequently, the mixture was internally mixed at 180 rpm for 30 min to ensure that the particles were evenly dispersed in the silicon matrix. The well-dispersed NF / silicon mixture was molded into a 22.86 mm × 10.16 mm × 2 mm 3 The samples were cured at 100°C for 25 min and were ready for electromagnetic measurements. Similarly, Nb2O5 / silicon mixtures and α-Fe2O3 / silicon mixtures were prepared using the same method and technology.

[0056] The specific analysis is as follows:

[0057] like Figure 3 As shown, Figure 3 (a) and Figure 3 (b) shows the complex dielectric constant and complex permeability (real and imaginary parts) spectra of Nb2O5 nanoparticles (NPs), α-Fe2O3 nanorods (NRs) and NF heterostructure nanocomposites in the frequency range of 8.2 to 12.4 GHz (X-band). The ε′ values ​​of all samples remain high and stable over the entire frequency range, and the ε′ value of the NF sample is about 22, reaching a peak. Similarly, the ε″ values ​​of all samples are relatively stable in frequency, but the NF sample exhibits some oscillatory behavior at low frequencies. For the Nb2O5 nanoparticles and α-Fe2O3 nanorod samples, the ε″ values ​​are large, indicating that their dielectric losses are relatively low, while the dielectric losses of the NF samples are small. The integration of Nb2O5 nanoparticles and α-Fe2O3 nanorods plays the role of tiny dipoles, which are polarized in the electromagnetic field, resulting in increased microwave absorption due to the increase in the complex dielectric constant. The low dielectric loss of the NF samples indicates its effectiveness in reducing energy dissipation, which will improve microwave absorption performance and enhance electromagnetic interference (EMI) shielding effectiveness.

[0058] Figure 3 (c) and Figure 3(d) in the figure shows the real and imaginary parts of the complex permeability (μ = μ′-jμ″) in the X-band. Some large fluctuations occur due to the natural resonance caused by the eddy current effect of the ferromagnetic particles and the enhanced surface anisotropy caused by the small size of the α-Fe2O3 nanorods. In addition, the higher anisotropy energy also contributes to the enhancement of microwave absorption. Due to the presence of magnetic components in the NF sample, the μ′ value is relatively lower than that of the sample composed only of Nb2O5 nanoparticles and α-Fe2O3 nanorods, which reflects the enhancement of electromagnetic energy loss. In addition, when the composite heterostructure with large interface polarization faces an alternating electromagnetic field, an electric current is excited, thereby forming a magnetic field opposite to the external electromagnetic field. Further, the generation of this opposite induced field will lead to magnetic field energy fluctuations, thereby contributing to the formation of a negative value of μ″.

[0059] Dielectric loss tangent (tanδ ε ) and magnetic loss tangent (tanδ μ ) are given by tanδ ε =ε″ / ε′ and tanδ μ =μ″ / μ′, such as Figure 4 As shown, it is demonstrated that Nb2O5 nanoparticles (NPs) and α-Fe2O3 nanorods (NRs) exhibit higher dielectric loss and magnetic loss compared to NF nanocomposites. In Nb2O5 and α-Fe2O3 samples, the dielectric loss is greater than the magnetic loss due to the weak magnetic properties of the composites. Therefore, the reflection loss mainly comes from the electrical loss, especially the magnetic loss is very small, indicating that the NF nanocomposites exhibit low losses, supporting their ability to store energy with minimal energy dissipation. This property makes the NF nanocomposites very suitable for applications such as capacitors, insulators, and other electronic components.

[0060] According to the Debye theory, the dielectric relaxation behavior of NF nanocomposites is described by the Cole-Cole plot, as shown in Figure 5 As shown in the figure, the Cole-Cole plots of Nb2O5 nanoparticles (NPs), α-Fe2O3 nanorods (NRs) and NF heterostructure nanocomposites are displayed. The semicircles in the figure are complex in shape, significantly distorted and overlapping, confirming the existence of multiple polarization relaxation mechanisms at the interfaces of these samples. Therefore, the dielectric losses associated with these different polarizations should be the main contributors to the electromagnetic (EM) losses in the composite. In addition, it was found that more linear tails of the semicircles can be observed only in the NF nanocomposite samples, indicating that the conductive losses caused by the conductive network developed in the NF nanocomposite cannot be ignored, as Figure 5 As shown in (c) in .

[0061] like Figure 6As shown, NF nanocomposites exhibit the lowest reflective shielding effectiveness (SE) in the entire X-band microwave frequency range. R ), is close to zero. This means that more than 99.999% of the electromagnetic (EM) energy entering the material is absorbed. R Based on the conductivity, lower conductivity will reduce the generation of eddy currents. Therefore, the energy of the electromagnetic wave field is reduced by ohmic electrothermal heating, and the reverse field is weaker, resulting in reduced reflection, thus improving the EMI shielding performance. Compared with other samples, the NF nanocomposite has a moderate conductivity, which makes it show the lowest SE R value.

[0062] In summary, two main loss mechanisms, mainly caused by the magnetic and conductive properties of Nb2O5 NPs and α-Fe2O3 NRs, dominate the attenuation of incident microwave energy in NF heterostructure nanocomposites. First, the electrical part of the electromagnetic field will be attenuated or absorbed. The conductive properties of Nb2O5 nanoparticles (NPs) and α-Fe2O3 nanorods (NRs) lead to the contribution of dielectric loss. These two mechanisms work together to effectively attenuate electromagnetic energy in NF heterostructure nanocomposites. In addition, the two metal oxides have unique synergistic effects, dipole polarization, interfacial polarization, microcapacitance effect and conductive loss, which provide a reasonable synthesis route for exploring advanced functional materials and open up a new research window.

[0063] Therefore, the present invention adopts the above-mentioned heterostructure composite material with high shielding effectiveness, preparation method and application, and synthesizes NF heterostructure nanocomposite material by double hydrothermal method. The synergistic effect of niobium pentoxide and trivalent iron oxide and morphology control significantly improve its overall shielding effectiveness, which has important value in the fields of modern electronics and technology.

[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a heterogeneous structure composite material with high shielding effectiveness, characterized in that: The following steps are involved: S1. Mix Nb2O5, FeCl3·6H2O and Na2SO4·10H2O in deionized water in a certain proportion to obtain a uniform solution; S2. The uniform solution obtained in S1 is transferred to a sealed container, subjected to a constant temperature heating treatment, and then subjected to an annealing treatment in an air environment to obtain a precipitate, which is cooled to room temperature, and then centrifuged and washed to obtain a NF heterostructure nanocomposite material.

2. The method for preparing a heterogeneous structure composite material with high shielding effectiveness according to claim 1, characterized in that: In S1, the mass ratio of the Nb2O5, the FeCl3·6H2O, the Na2SO4·10H2O and the deionized water = 0.05-0.15g: 0.01-0.02g: 0.05-0.07g: 25-35ml.

3. The method for preparing a heterogeneous structure composite material with high shielding effectiveness according to claim 1, characterized in that: In S2, the constant temperature heating treatment is specifically: Maintain the temperature within the range of 160°C to 200°C for 10h to 14h.

4. The method for preparing a heterogeneous structure composite material with high shielding effectiveness according to claim 1, characterized in that: In S2, the annealing treatment is specifically: Annealing is performed at a heating rate of 1°C / min to 3°C / min in a temperature range of 450°C to 550°C for 2h to 4h.

5. The method for preparing a heterogeneous structure composite material with high shielding effectiveness according to claim 1, characterized in that: In S2, the washing is performed multiple times using ethanol and deionized water.

6. A NF heterostructure nanocomposite material prepared by the method for preparing a heterostructure composite material with high shielding effectiveness as claimed in any one of claims 1 to 5.

7. Use of the NF heterostructure nanocomposite material as claimed in claim 6 in capacitors, insulators and other electronic components.

8. The use according to claim 7, characterized in that: The NF heterostructure nanocomposite material was embedded in a silicone elastomer matrix by mechanical mixing and solution mixing techniques to obtain a sample for electromagnetic shielding.

9. The use according to claim 8, characterized in that: The following steps are involved: Step 1: Mixing a polymer matrix and a curing agent in a certain proportion to prepare a silicon solution; Step 2: Add the NF heterostructure nanocomposite material into the silicon solution, perform dispersion treatment and then solidify to obtain a sample.

10. The use according to claim 9, characterized in that: Step 2 is as follows: The NF heterostructure nanocomposite was incorporated into the silicon solution and internally mixed at 180 rpm for 30 min to obtain a NF / silicon mixture with particles uniformly dispersed in the silicon matrix, and then cured at 100 °C / min for 25 min to obtain a NF heterostructure nanocomposite / silicone elastomer.

Citation Information

Patent Citations

  • Ferromagnetic-antiferromagnetic thin film heterojunction structure, fabrication method thereof and magnetic storage device

    CN105609630A

  • Rod-like NiO / alpha-Fe2O3 compound gas sensitive material and preparation method and application thereof

    CN109264796A

  • Ferroniobium intermediate alloy and preparation method and application thereof

    CN111378883A

  • Heat-conducting shielding composite material with double-isolation network structure and preparation method of heat-conducting shielding composite material

    CN115521635A

  • Electromagnetic shielding material, thin film and preparation method thereof

    CN115991475A